2021
DOI: 10.7759/cureus.12832
|View full text |Cite
|
Sign up to set email alerts
|

Can Ferritin Levels Predict the Severity of Illness in Patients With COVID-19?

Abstract: Objectives: This study aimed to investigate whether ferritin level can predict the severity of coronavirus disease 2019 (COVID-19). Background: The COVID-19 pandemic has been challenging for both patients and caregivers. Many laboratory markers have been used to better understand the causes of poor outcomes and to improve the management of COVID-19 patients. Methods: A total of 93 patients who had a positive polymerase chain reaction test result for severe acute respiratory syndrome coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…This may have been due to the fact that the questionnaire did not ask whether they had had the disease before or after vaccination against SARS-CoV-2. Similar results were found in a study done in Saudi Arabia [41], and another in Helsinki [42].…”
Section: Vaccination Coverage Against Sars-cov-2supporting
confidence: 91%
“…This may have been due to the fact that the questionnaire did not ask whether they had had the disease before or after vaccination against SARS-CoV-2. Similar results were found in a study done in Saudi Arabia [41], and another in Helsinki [42].…”
Section: Vaccination Coverage Against Sars-cov-2supporting
confidence: 91%
“…In a meta-analysis, Henry et al [39] discovered that ferritin levels in hospitalized patients were significantly higher, which could be a predictor for serious disease development. In a study on mild and severe patients, Bozkurt [40] discovered that an AUC of 88 and a cutoff of 264.5 ng/mL for ferritin levels could be used to predict disease severity. Cao et al [41] reported that the cutoff value of 272.5 ng/mL for ferritin levels (AUC = 87.3) could be used in estimating disease severity upon admission.…”
Section: Discussionmentioning
confidence: 99%
“…Reports that suggest the role of ferritin in COVID-19 prognosis have certain limitations, such as they are not inclusive of all ethnicities, the sample size was not large enough, and only hospitalized cases were studied. Nonetheless an early analysis of serum ferritin levels might help to predict disease severity in COVID-19 patients (Bozkurt et al 2021 ). A possible approach to lower serum ferritin levels is the use of iron chelators.…”
Section: Ferritinmentioning
confidence: 99%